ALIENASI VERBAL PADA UMAT KATOLIK ETNIK MANGGARAI - Pius Pampe (Program Magister Linguistik Universitas Udayana, 2009)
Anstract Catholics of Manggarai ethnic (UKEM) in the district of Manggarai have experienced a verbal alienation due to an awkward Manggarai language (ML) used in Catholic religus activities (K3). As native speakers of ML, people even do not understand such an awkward language. Furthermore, they do not find any value behind the usage of such a language. Statistically, their comprehension on such a language is only 43,22%, wich is categorized as do not comprehend. Religious meaning and value wich are not comprehended consist of love, faithfulness, unity, and peace. The contributing factor of such a condition is that the ML used in K3 with religious meaning and value has uniqueness in such aspects as forms, superstructures, and passage-micro structures. The uniqueness in the first aspect is indicated by monolog passage in horizontal dimension, while the second’s by the passage consisting of introduction, pre-core, core, pre-closing, and conclusion, each of witch has communication content. In the terms of micro structures, the uniqueness is indicated by the use of allophones [o] and [i], as well as alliteration, rhytme, assonance, and parallelism related to human’s body and plants.